The differences between sex offenders who victimise older women and sex offenders who offend against children - Browne, Kevin D.; Hines, Morag; Tully, Ruth (Taylor & Francis, 2016)
Objectives: Within the literature on sex offending, much attention is paid to the distinction between those sex offenders who offend against adults and those who offend against children. In contrast, there is a paucity of research into sex offenders who offend specifically against elderly or older victims. Method: A detailed interview and psychometric tests were conducted with a sample of 28 sex offenders who had been convicted of a sexually motivated offence against an older female. These data were compared to a sample of 23 child sex offenders. Results: Results indicate that amongst other significant differences between these sub-groups, men who offend against older women are generally younger, are more violent, and are more likely to use a weapon and cause injury and death compared to child sex offenders. The men who offended against children were more likely to think about and plan their offending, spend more time with the victim pre and post offence, admit sexual arousal during the offence, and admit to a sexual motivation for the offence. Conclusions: This study suggests that men who sexually offend against older women and men who sexually offend against children are distinct groups. Treatment and risk management strategies should take this into account. Further exploration of this sub-group of offenders is recommended to help inform treatment and risk management strategies for sex offenders who offend against older people.